Research and synthesis of the automatic water level control system of the mine water tank according to the criterion of minimizing the dispersion of fluctuations of power consumption - Bublikov, A.; Isakova, M.; Nadtochyi, V.; Zybalov, D.; Halchenko, Yu.; Khoroshailov, M. (Видавництво НТУ "ДП", 2022)
The purpose is to increase the efficiency of the process of automatic control of the water level in the mine reservoir due to the improvement of the automatic control algorithm. The main indicator of the quality of the system of automatic control of the water level in the mine reservoir is the minimization of the dispersion of fluctuations in the total power consumed by the pumps of the station. Research methodology. The tasks are solved using the method of computational experiments with the use of specialized computer programs for modeling the process of controlling pumps in the reservoir. To study the automatic control system, theoretical research methods were used, namely, analysis and synthesis of the system based on the modern theory of automatic control, as well as systems analysis. Evaluation of the effectiveness of the automatic control process was carried out using the methods of mathematical statistics.
Дослідження та синтез системи автоматичного керування рівнем води у шахтному водозбірнику за критерієм мінімізації дисперсії коливань споживаної потужності
Keywords: synthesis of the automatic control system; mine reservoir; water level; синтез системи автоматичного керування; шахтний водозбірник; рівень води